Flow‐independent 3D whole‐heart vessel wall imaging using an interleaved T2‐preparation acquisition. Issue 1 (5th March 2012) - Andia, Marcelo E.; Henningsson, Markus; Hussain, Tarique; Phinikaridou, Alkystis; Protti, Andrea; Greil, Gerald; Botnar, Rene M.
Abstract Current techniques to visualize the arterial vessel wall are limited in coverage because most of them are flow dependent. In this study, we present a novel technique for flow‐independent vessel wall imaging that takes advantage of the differences in T2 relaxation time of arterial blood and surrounding tissues using the T2‐preparation prepulse. The technique is based on the acquisition and subtraction of two data sets, one obtained with and one without T2‐preparation prepulse. This approach allows for nulling the signal of arterial blood while maintaining signal from muscle and vessel wall. The result of the subtraction is a flow‐independent black‐blood vessel wall image. To minimize the motion sensitivity of the subtraction step, we developed an interleaved acquisition for the T2‐preparation prepulse and non‐T2‐preparation prepulse images, which allows obtaining coronary vessel wall images from a whole‐heart acquisition with minimal misregistration artefacts. In this article, we present the technique and preliminary results in healthy subjects. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.